Pola Manajemen Dakwah Mesjid Al Munawwaroh Sayati, Margahayu Kab. Bandung - Rima Mugia Restu Lestari; Hendi Suhendi (Jurnal Riset Komunikasi Penyiaran Islam, 2021)
Abstract. Management patterns in an organization are very important in carrying out a plan. The mosque management pattern is very important as an effort to improve the mosque from within the form of strengthening the existence of the mosque as a place of worship for Muslims. AL Munawwaroh Mosque is one of the mosques built in Sayati village, Bandung district. The existence of this mosque has been known by several outside congregations and in the implementation of its management there have been many developments from time to time, especially in the aspect of Islamic da'wah activities. The author examines how the Management Pattern of the AL Munawwaroh Mosque in increasing Islamic da'wah activities. The purpose of this study was to determine the management pattern of the al Munawwaroh mosque in increasing its preaching activities. The benefit of this research is to enrich the scientific treasures of management and sran for the improvement of other mosques. Research conducted by the author is a case study researcher with a qualitative approach, in order to provide clarity on the problem or event under study. Thus the population of this research is the management of the Al Munawwaroh Mosque, the congregation, and community leaders. This study uses interview data collection techniques, observation, and documentation. Interviews were conducted with mosque administrators who were directly involved with the applied management of the mosque. The results of the study found that first, the management pattern carried out by the management of the AL Munawwaroh Mosque was the planning, organizing, implementing, and monitoring patterns. Where all the patterns above are carried out together by the board, the congregation. Second, Islamic da'wah activities carried out by the Al Munawwaroh mosque are in accordance with what has been planned in the management pattern. Third, the management of the Al Munawwaroh mosque from the start of construction, finance, and daily worship services is quite good. Abstrak. Pola manajemen dalam sebuah organisasi sangatlah penting dalam menjalankan sebuah perencanaan. Adapun pola manajemen masjid sangat penting sebagai suatu upaya perbaikan masjid dari dalam berupa penguatan eksistensi masjid sebagai tempat peribadahan umat islam. Masjid AL Munawwaroh merupakan salah satu masjid yang dibangun di desa sayati kab bandung. Keberadaan masjid ini sudah dikenal oleh beberapa Jemaah luar dan dalam pelaksanaan manajemennya sudah banyak perkembangan dari masa ke masa, khusunya pada aspek aktivitas dakwah islam. Penulis meneliti bagaimana Pola Manajemen Masjid AL Munawwaroh dalam meningkatkan aktivitas dakwah islam. Tujuan penelitian ini adalah untuk mengetahui pola manajemen yang dilakukan masjid al Munawwaroh dalam meningkatkan aktivitas dakwahnya. Manfaat penelitian ini untuk memperkaya khazanah keilmuan manajemen dan sran bagi perbaikan masjid lainnya. Penelitian yang dilakukan oleh penulis merupakan penelitia studi kasus dengan pendekatan kualitatif, guna memberikan kejelasan terhadap masalah atau peristiwa yang diteliti. Demikian yang menjadi populasi peneliti ini adalah pengurus Mesjid Al Munawwaroh, Jemaah, dan tokoh masyarakat. Penelitian ini menggunakan teknik pengumpulan data wawancara, observasi, dan dokumentasi. Wawancara yang dilakukan kepada pengurus masjid yang terlibat langsung dengan manajemen masjid yang diterapkan. Hasil penelitian menemukan, bahwa yang pertama, pola manajemen yang dilakukan oleh pengurus Mesjid AL Munawwaroh ialah dengan Pola Perencanaan, pengorganisasian, Pelaksanaan, dan pengawasan. Dimana semua pola diatas dilakukan bersama oleh pengurus, Jemaah. Kedua, aktivitas dakwah islam yang dijalankan oleh masjid Al Munawwaroh sesuai dengan apa yang telah direncanakan pada pola manajemen. Ketiga, pengelollan masjid Al Munawwaroh dari mulai pembangunan, keuangan, sera ibadah harian sudah cukup baik dilaksanakan.